Battery Durability and Reliability under Electric Utility Grid Operations: Path Dependence of Battery Degradation. Issue 10 (12th June 2019) - Baure, George; Devie, Arnaud; Dubarry, Matthieu
Abstract : With the deployment of more and more large batteries on the grid addressing different applications, it is essential to better understand their degradation pattern and to accurately forecast their durability. In this work, the electrochemical data from a laboratory testing experiment replicating real usage was extensively investigated using incremental capacity and variance analyses. Results showed that the degradation of these cells is much more complex than what the capacity loss and the resistance increase indicated. A significant amount of "silent" degradation was uncovered. This silent degradation was quantified and forecasted to induce, in some cases, an acceleration of the capacity loss.